FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PARTISIPASI MASYARAKAT PADA PROGRAM BANK SAMPAH DI KECAMATAN TAMPAN RIAU - Fajriah, Risyda; ", Nurhamlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This reseach is titled “The Factors which influence to the society participation on the garbage bank program in the district Tampan of Pekanbaru City”. The purpose of this research to know the level of society participation on the gerbage bank program pekanbaru city. As for the method used in this research is descriptive quantitative method. The population in this study is namely gerbage bank costumer with the number of samples 62 respondents. Variabel in this study is education,profession,family income, and long stay (domicile). Data is analized with product moment correlation. Based on the results of the study, the level of society participation on the waste program in the category of “ medium” is 67,74% while the”high” category is only 22,58%, and factors which influencer to the society participation on the waste in the district Tampan of Pekanbaru City is Education with R value of 0,278, Profession with R value -0,166, Family Income with R value -0,181,and long stay (domicile) with r value of -0,238. Keyword: Participation, Gerbage Bank, Society